Evaluation of strategies for the occupational health risk assessment of chemical toxicants in the workplace based on a quantitative analysis model - Xu, Qiuliang; Zhang, Meibian; Xu, Lingtong; Yuan, Weiming; Ren, Hong; Wang, Peng; Shao, Xincun; Zhou, Zhen; Zou, Hua; Cao, Yiyao (Frontiers in Public Health, 2022)
Objectives The commonly used methods for the occupational health risk assessment (OHRA) of chemical toxicants cannot fully meet the needs of practical work. This study evaluated OHRA strategies for chemical toxicants in the workplace by establishing a quantitative analysis model. Methods Five typical industries in China that implement OHRA using the six common models (the Environmental Protection Agency, Australian, Romanian, Singaporean, International Council on Mining and Metals, and the Control of Substances Hazardous to Health models) were selected as the research objects. We established a quantitative analysis model to compare the six models and applied it to compare the results obtained using each model and preliminarily analyze the advantages, limitations, and application scope of each method. Results The risk ratio (RR) values of the six methods decreased in the following order: RREPA > RRCOSHH > RRICMM > RRAustralia > RRSingaporean > RRRomanian (P < 0.05). Among the six models, the Singaporean model had the strongest RR correlation with the other models (P < 0.01). The sequence of RRs obtained from the Singaporean, ICMM, Australian, and Romanian models in the five industries was consistent with the sequence of the three inherent risk levels in those industries. Only the Romanian model could distinguish between the RRs of all five industries. The EPA and Singaporean models could effectively distinguish the differences in inherent risk for four hazard factors (manganese and inorganic compounds, benzene, xylene, and ethyl acetate), with the assessment accuracy being relatively higher for the EPA model. Conclusions Among the six models, the EPA model had the relatively highest accuracy in assessing chemical toxicants, followed by the Singaporean model. The EPA and Romanian models were strongest in differentiating the differences in toxicity risk. More studies on OHRA methodology are needed.